School teachers' time management in classroom - Ilias, Nor Ildahayati; Mohd Ali, Hairuddin (2013)
workload and the core business of teaching. Hence, there were too many clerical works related to the management of the pupils although its about organizing the day, organizing the classroom, deciding how long and how often to teach various subjects, recording student progress in academic, or keeping time consuming behavior problems to a minimum. This paper presents an evaluation of teachers’ percentage of spending time for teaching and learning in the classroom in three sections. It provides the models of the Pre-Delivery Time Management (PreDTM), Delivery Time Management (DTM) and Post-Delivery Time Management (PostDTM). This increase the effectiveness of teachers in organizing and managing their time in classroom. The objective of this study is to create the awareness amongst teachers about their time management in classroom and the effect of having well managerial with the student’s achievement. This research is quantitative in nature that explaining the general conceptual model of the study. Thus, findings from 90 teachers from Sekolah Kebangsaan Sungai Pelong, Sungai Buloh, Selangor would be of benefit to other teachers as well as Kementerian Pelajaran Malaysia generally.